PENGARUH MARKETING CAMPAIGN WAKTU INDONESIA BELANJA DAN BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMENDI TOKOPEDIA - Natasya Eka Putri Tobing; Hafiza Adlina (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Indonesia is the country with the most e-commerce users in the world with an estimated transaction value in 2022 reaching IDR 476.3 trillion. This causes many e-commerce companies to compete with each other to lead the market in Indonesia, including Tokopedia as an e-commerce company from Indonesia. Therefore, Tokopedia needs to create various strategies to win the competition. This research aims to determine the influence of the #WaktuIndonesiaBelanja marketing campaign on purchasing decisions at Tokopedia, determine the influence of brand equity on purchasing decisions at Tokopedia, and determine the influence of the #WaktuIndonesiaBelanja marketing campaign and brand equity on purchasing decisions at Tokopedia. This research uses quantitative research with an associative approach. The population in this study were Medan City students who used Tokopedia and the sample was determined to be 100 respondents with a sampling technique using purposive sampling. The data collection technique in this research uses primary data obtained by distributing questionnaires directly and via Google Form, while secondary data is obtained through literature study. The data analysis methods used are descriptive analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this research conclude that the marketing campaign #WaktuIndonesiaBelanja (X1) and brand equity (X2) have a significant partial and simultaneous (together) effect on purchasing decisions (Y). The results of the coefficient of determination test show that there is a fairly strong relationship between the #WaktuIndonesiaBelanja marketing campaign and brand equity on purchasing decisions on Tokopedia with a correlation coefficient (R) of 0.729. The Adjusted R Square value in this research shows that the marketing campaign variable #WaktuIndonesiaBelanja and brand equity can explain the purchasing decision variable by 52.1%